Fruit marketing, its efficiency and supply chain constraints in India: A case study - CHAND, KHEM; SURESH, A; DASTAGIRI, M B; KUMAR, SHALANDER; MANDAL, SUBHASIS (The Indian Journal of Agricultural Sciences, 2021)
Study investigated the agribusiness opportunities, marketing channels and marketing efficiency of different supply chain systems for two important fruit crops kinnow and aonla (Indian gooseberry) in Rajasthan. Two districts, viz. Sriganganagar and Jaipur, having highest area under cultivation of these crops in the state, were purposively selected. Information was collected from 120 farmers, 30 wholesalers (traders/Contractors) and 30 retailers during the year 2009-2011 for both the crops. Further 25% of sample households were again revisited during 2019-20 to find changes in marketing of these selected fruit crops. The producers’ share in consumer’s rupee was 32% and 28% for kinnow and aonla, respectively. The marketing efficiency index in dominant channel was 0.48 in kinnow and 0.38 in aonla. The most common and important constraint in marketing of fruits was cartelisation among traders. The imperfect market structure forces the farmers to enter into a forward contract that sets a minimum price, rather at the dissatisfaction of the farmer, as an insurance against possible lower price at later stages. Establishment of multi-fruit processing units in production area, development of infrastructure at major market centres, and establishing export value chain for kinnow and necessary support/incentives for orchard management for timely disposal of kinnow fruits are suggested as strategies to improve the marketing efficiency.